Pengaruh Promosi Terhadap Keputusan Menabung Nasabah - Herid Apner Aflili; John A. F. Kalangi; Olivia Walangitan (Universitas Sam Ratulangi, 2017)
PT.Bank Papua Branch Manado realizes that In the course of Bank Papua in the world of national banking, not apart from efforts to increase the mobilization of public funds through a series of government policies in terms of banking monetary, with the target of achieving an increase in the number of customers. Looking at these conditions, all banking institutions including Bank Papua compete and compete to market savings products that can meet the needs of society.This study is categorized as the type of survey research where the information collected was obtained from the respondents by using the questionnaire as a basic data collection tool. Furthermore this research includes the type of explanatory research, where the type of research only focuses on problems that have occurred or that is happening by highlighting the relationships between research variables.From the above calculation, it can be concluded that there is influence of X variable to variable Y for 18% and the rest of which 82% influenced by other factors not examined by researchers such as interest factors, environmental factors, location factors and individual economic conditions.In suggesting PT.Bank Papua Manado Branch Office to keep improving promotional activities undertaken by him because it is good and proven, based on test results conducted in this study.Â Keywords: Promotion, Savings Decision